Goodword islamic studies: grade 1 - Khan, Saniyasnain (GOODWORD BOOKS New Delhi, 2022)
A comprehensive resource aimed at enhancing understanding of Islamic teachings for students, featuring engaging lessons and activities. It encourages critical thinking and moral development in young readers.